Determinants of Bank Profitability and Implications for Company Value with Moderating Dividend Policy - Sutiman, Sutiman; Suteja, Jaja; Anwar, Mokhamad; Rachmawaty, Rachmawaty (Owner : Riset dan Jurnal Akuntansi, 2024)
The research is quantitative and the objective is to determine the internal (Loan Quality, Third Party Fund, Managerial Efficiency) and external (BI Rate, Inflation) variables that determine Bank profitability, and the impact of this profitability on company value by moderating the Bank's stock dividend policy. The method used is panel data regression and moderated regression analysis using Eviews 10. The data used is secondary data with a sample of 10 Book 4 banks listed on the Indonesian Stock Exchange for the 2011-2020 period. The results obtained are first Loan Quality, Third Party Funds, Managerial Efficiency, Bank Indonesia Interest Rates and Inflation Rates simultaneously have a significant and positive effect on Banking Profitability, second Banking Profitability partially has a significant and positive effect on Company Value and third Banking Profitability which is moderated by Dividend Policy partially has a significant and positive effect on Company Value